Investigation concerning the Radiation Exposure of the Medical Personnel during F-l8-FDG-PET Studies - Linemann, H.; Will, E.; Beuthien-Baumann, B. (Nuklearmedizin - NuclearMedicine, 2000)
Aim: The aim of the investigation was the identification of those working steps with the highest radiation exposure for the medical personnel during F-l8-FDG-PET studies and to evaluate the effectiveness of radiation protection devices and instructions developed in our PET-center. Methods: The personal dose and hand dose were measured for each working procedure during F-l8-FDG-PET studies using electronic personal dosimeters and thermoluminescent dosimeters respectively. Additionally, measurements of the radiation level near the patient were taken. Results: The mean personal dose resulting from syringe preparation was 1 μSv/syringe, from injection 3 μSv/patient, from blood sampling during quantitative studies 6 μSv/study, and from positioning and handling of the patient 6 μSv/study. The mean hand dose per syringe preparation was 710 μSv for each hand. The mean hand dose during injection was 13 μSv for the right hand and 27 μSv for the left hand. All above mentioned values were measured applying the routine radiation shielding in use in our PET center. Conclusion: With the developed radiation shielding and means to reduce radiation exposure applied the allowed annual dose for medical personnel are not exceeded. One exception is the hand dose resulting from syringe preparation. An automatic or remote filling device should be used at this working step.
Keywords: PET; radiation exposure; personnel dose; hand dose; radiation shielding